Clause Typing and Feature Inheritance of Discourse Features. (27th September 2016) - Lochbihler, Bethany; Mathieu, Eric
Abstract: The aim of this article is twofold. First, we claim that δ‐features (discourse features), as well as ϕ‐features, can be inherited from C to T (Richards 2007, Chomsky 2008), as shown by wh ‐agreement on T in Ojibwe (Algonquian). Our analysis supports Miyagawa's (2010) hypothesis that discourse and agreement features are two sides of the same coin, which can be distributed differently crosslinguistically. Second, we propose that although ϕ and δ typically bundle together on a single C head, this is not the case in all languages and in fact will vary parametrically. Ojibwe clause typing is partitioned between agreement/ϕ‐features on independent order (i.e., plain matrix) C and discourse/δ‐features on conjunct order (e.g., embedded) C. This parameter, that certain features may or may not bundle on C, captures a significant cluster of properties in Ojibwe: Initial Change, lack of person prefixes in the conjunct order in contrast with the independent, as well as the availability of long‐distance agreement. Our proposal supports the idea that much crosslinguistic variation reduces to the distinct feature structures making up functional heads, such as v, D, and C, rather than to primitives.